Disease-specific quality indicators, guidelines, and outcome measures in vasculitis. - Mukhtyar, C; Luqmani, R (2007)
Measuring quality of care in the anti neutrophil cytoplasm antibody (ANCA) associated vasculitides (AAV) has become more complex, because the introduction of immunosuppressive therapy has resulted in a substantial improvement in survival. Early diagnosis remains a problem, because many patients are seen by non-specialists who may not recognize vasculitis or fail to initiate therapy promptly. A comprehensive assessment to determine the pattern and severity of organ involvement allows a specialist to plan a therapeutic regimen, and to manage co-morbidity effectively. Recent guidelines from the European League Against Rheumatism (EULAR) address the conduct of high-quality clinical trials in vasculitis. Risk factors for poor outcome in vasculitis are probably similar in the different forms of AAV. The risk factors are discussed in the context of failing to achieve remission, relapse, organ failure, and death. Factors indicating a poor prognosis include: the presence of high disease activity at diagnosis (which increases mortality risk even though it is associated with a greater likelihood of response to therapy); the pattern of organ involvement, for example with cardiac features carrying an adverse outcome in Wegener's granulomatosis; significant damage; renal impairment; persistence of ANCA; elderly age at diagnosis; under-use of cyclophosphamide and glucocorticoids in the first 3 months of treatment; persistent nasal carriage of Staphylococcus aureus; and the increased risk of bladder cancer in patients who are given large amounts of cyclophosphamide.